Oxidative Imbalance And Risk Factors Involved In Premalignant And Malignant Lesions Of The Uterine Cervix - Heredia-Ruiz, Danay; Herrera Martínez, Manuela; Fernández Caraballo, Douglas; López Ocampo, Lázara Gladys; Estévez Cobo, Luis Alfredo; Santana Rodríguez, Sergio; González Rodríguez, Emilio (Revista Cubana de Investigaciones Biomédicas, 2019)
Objetive: to determine the indicators of oxidative stress and risk factors in patients with premalignant and malignant lesions of the cervix. Methods: A total of 150 women were studied: 40 with low-grade squamous intraepithelial lesion, 40 with high-grade squamous intraepithelial lesion, 40 with stage IIB squamous cell carcinoma and 30 with negative cytology taken as a control, from the Gynecology Service of the “Chiqui Gómez” Polyclinic, and Oncology Service “Celestino Hernández” Hospital of Santa Clara, aged between 19 and 70. The information on the risk factors was obtained through an individualized interview, and oxidative stress indicators were determined by spectrophotometric techniques. The comparison and association between groups was carried out with the support of the statistical program SPSS. Results: The levels of antioxidant enzymes showed a significant decrease in both groups of squamous intraepithelial lesion, glutathione decreased significantly in the three groups of lesions, while malonildialdehyde significantly increased in the same groups with respect to the control. The risk factors with the highest incidence in the affected women were early sexual contact, the number of sexual partners, the use of oral contraceptives, exposure to environmental toxins and the habit of smoking. Conclusions: There is an oxidative imbalance in the cases due to the decrease of the antioxidant enzymatic system, where the reduced levels of glutathione contribute to the increase of the lipid peroxidation. Risk factors may influence exposure to the papilloma virus and lead to the development of premalignant and malignant lesions in the cervix.